New bismuth‐containing quadruple therapy in patients infected with Helicobacter pylori: A first Italian experience in clinical practice. Issue 3 (26th January 2017) - Tursi, Antonio; Di Mario, Francesco; Franceschi, Marilisa; De Bastiani, Rudi; Elisei, Walter; Baldassarre, Gianluca; Ferronato, Antonio; Grillo, Simone; Landi, Stefano; Zamparella, Maria; De Polo, Manuela; Boscariolo, Laura; et al.
Abstract: Background: Rising antibiotic resistance requires the evaluation of new and effective therapies. Aims: To test the efficacy and safety of the new bismuth‐containing quadruple therapy in patients infected with Helicobacter pylori . Material and Methods: Consecutive H. pylori ‐positive dyspeptic patients were enrolled, either naïve or with previous failure treatment. Patients were treated with Pylera ® (three‐in‐one capsules containing bismuth subcitrate potassium 140 mg, metronidazole 125 mg, and tetracycline 125 mg) three capsules q.i.d. plus omeprazole 20 mg or esomeprazole 40 mg b.i.d. for 10 days. Eradication was confirmed using an urea breath test (at least 30 days after the end of treatment). Efficacy was assessed by UBT and safety by means of treatment‐emergent adverse events. Results: One hundred and thirty‐one patients were included in the study: 42% of patients were naïve, and 58%, with previous failure treatment. H. pylori eradication was achieved in 124 patients (94.7%, 95% confidence intervals (CIs) 89.3‐97.8) in ITT population. In the PP population, the percentage was 97.6% (95%, CIs 93.3‐99.2). No difference in eradication rate was found either between naïve and previously treated patients (92.7% vs 96.0%, P =.383), or smoking and nonsmoking ones, or in patients taking omeprazole or esomeprazole. Treatment‐emergent adverse events occurred in 35 patients (26.7%, 95% CIs 19.9‐34.9). They were mild in all cases except in four, who discontinued the study due to diarrhea (three patients) and diffuse urticarial rush (one patient). Conclusions: Pylera ® achieved a remarkable eradication rate in clinical practice, irrespective if it was used as first treatment or as a rescue therapy. Treatment‐emergent adverse events were uncommon generally mild.